Prayer and Health: An Interdisciplinary : (Study of the Qur’an and Hadith) - Muhammad Robby; Arini Rochyati; Novi Nazilatur Rohmah (International Journal of Islamic Educational Research, 2025)
Interdisciplinary studies linking the Quran and Hadith with modern science continues to attract significant attention among global academics. This phenomenon reflects a paradigm shift in Islamic studies, where integration with contemporary disciplines is seen as essential for a more comprehensive understanding. Prayer holds a central place in Islamic teachings, recognized as one of the five fundamental pillars of Islam. The concept of health in Islam is broad, encompassing physical, emotional, and spiritual aspects in an integrated manner. This holistic Islamic view of health demonstrates that the practice of worship, particularly prayer, has the potential to provide health benefits that extend beyond the physical dimension. Prayer contributes significantly to an individual's overall mental and spiritual well-being. The aim of this study was to understand the integration of prayer and health through an interdisciplinary study linking the Koran and Hadith. The study concluded that there is a significant and multifaceted relationship between the practice of prayer and various aspects of health, encompassing the physical, mental, and spiritual dimensions. This demonstrates that religious teachings do not focus solely on the spiritual aspect but also provide a comprehensive framework for maintaining overall health.